Pluriversal Politics and Transnational Regional Localization: Alternative Developments in World Societies - Ananta Kumar Giri (Universitas Islam Internasional Indonesia (UIII), 2026)
This article explores pluriversal politics as an alternative in contemporary politics and international relations which can help us understand contemporary Muslim societies and their challenges. The article explores the dynamics of transnational regional localization, where processes of localization, regionalization, and trans-nationalization meet in complex, creative, and emergent ways. Here, it examines the work of the Spirit of Bandung, the Association of Southeast Asia Nations (ASEAN), and Brazil, Russia, India, China, and South Africa (BRICS), and calls for understanding emergent multi-alignment and multiplexity in our world, going beyond declining unipolarity and multipolarity. The article then discusses how contemporary world society calls for dialogues among religions, civilizations, cultures and civilizations to go beyond the contemporary logic and practice of domination and one-sided assertion. It brings the vision and practices of inter-religious and trans-civilizational dialogues to the discourse of pluriversal politics, international relations, world system studies and the multi-dimensional visions and practices of Muslim politics in our contemporary world. It also argues how regional and global formations such as ASEAN and BRICS need to focus more on inter-religious and trans-civilizational dialogues.